Preparação, caracterização e comportamento mecânico de compósitos híbridos à base de resina epóxi/fibra visando à produção de juntas por enrolamento filamentar - Faro, Ana Angélica dos Santos (2012)
Joints represent a discontinuity in the homogeneity of the material that results in localized tensions which often starts failure becoming inevitable introduced in piping systems. The extensive use of composite materials in piping systems is still limited and this is due to the need to study new types of joints for composite pipes connections, and the study of fibers used and their arrangement, the resin to be used, and mechanical behavior of materials and joints to failure. The work aims to prepare, characterize and evaluate the performance of the hybrid composites based on epoxy resin / fiber using coir dust as filler for application in production of joints by filament winding. Specimens were produced from two polymer systems based on epoxy (DGEBA) with different cure cycles containing different percentages of filler. Then, unidirectional hybrid composites were produced: resin/filler/glass "E" fiber and resin/filler/carbon fiber. The characterization of materials and the effect of the addition of filler were carried out using tensile tests, thermal analysis (differential scanning calorimetry, thermogravimetry and dynamic mechanical analysis), Fourier transform infrared, optical microscopy and scanning electron microscopy. Finally, composite joints were produced using the technique of filament winding, and their performance in connection composite tubes tested under hydrostatic pressure. The presence of filler at epoxy resins modifies the viscoelastic and mechanical properties, and failure modes, but does not affect the degradation profile and the cycle of cure. The hybrid composite of carbon fiber and epoxy resin cured at room temperature showed improvement in tensile properties, about 37.5%, for the addition of 10% filler, which is not observed for the other composites. The joints produced with glass E fibers and epoxy resin had a performance 13% lower, on average, than the standard tube, and the typical failure mode was leakage varying the failure s location.